Decreasing the Level of Depression in Adolescent Girls through Self Hypnosis at SMPN 3 Abiansemal - Luh Putu Widiastini; I Gusti Agung Manik Karuniadi; Ni Made Egar Adhiestiani (Universitas STRADA Indonesia, 2025)
Adolescence is a crucial period of social and emotional development that affects mental well-being. However, many adolescents experience emotional disorders, such as anxiety and depression. Based on WHO data (2021), around 2.8% of adolescents aged 15-19 years experience depression, with a higher incidence in girls. Various factors, such as academic pressure, hormonal changes, and social and family problems, are often the main triggers of depression in adolescent girls. If not handled properly, this condition can have a negative impact on development and quality of life. This community service method begins with Socialization, Pretest, Lecture plus Method, Demonstration and role play self-hypnosis method, and posttest on the 7th day on 75 adolescent girls at SMPN 3 Abiansemal. This community service shows that self-hypnosis contributes to reducing depression in adolescent girls. Research using the Wilcoxon Signed-Rank Test showed a decrease in depression levels after self-hypnosis therapy (p = 0.013). Although several studies support its effectiveness, more scientific evidence is needed to confirm its clinical benefits. However, self-hypnosis has the potential to be an alternative strategy that can help young women cope with depression and improve mental health.